Electrical grid reliability assessment by fault tree analysis - Ahmed Agwa; Zaky Matter; Ezzat Eisawy; Hamdy Hassan (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The main rule of an electrical grid is to supply electrical energy to consumers as economically as possible, and with an adequate degree of reliability. Reliability is an essential measure and important component of all power system planning and operation procedures. In this paper, the electrical grid reliability is evaluated by Fault Tree (FT) analysis. In this method Alternating Current (AC) load flow analysis is combined with the FT technique. The electrical grid reliability is calculated based on the unreliability of the power supplied to the loads. The verification of the method is performed on a part of the Egyptian electrical grid (Alexandria zone 17-bus). The electrical grid components are sorted according to their influence on the electrical grid reliability.